Parler ou ne rien dire : La prise de parole en classe d’anglais Lansad - Elisabeth Crosnier; Nicole Décuré (Recherches en didactique des langues et des cultures)
Oral expression in English is now at the center of teachers’ concerns, including in the ESP sector which is still, on this particular issue, fairly unexplored. In this paper, we present the results of a survey based on a questionnaire submitted to a sample of science students in ESP courses. The aim of this research was to evaluate each student’s speech production to get a better picture of what is actually happening in a class that is supposed to be focused on oral skills. The study identifies both positive and negative factors influencing oral production in order to suggest remedial means of improving the situation.